A nation of families: traditional indigenous kinship, the foundation for Cheyenne sovereignty. (March 2019) - Killsback, Leo Kevin
One of the major destructive forces to American Indian peoples were the assimilation-based policies that destroyed traditional kinship systems and family units. This destruction contributed to the cycle of dysfunction that continues to plague families and homes in Indian country. A second major destructive blow occurred when colonial forces, through law and policy, reinforced white male patriarchal kinship and family systems. In this colonial system, American Indian concepts, roles, and responsibilities associated with fatherhood and motherhood were devalued and Indian children grew up with a dysfunctional sense of family and kinship. This article examines the traditional kinship system of the Cheyenne Indians, highlighting the importance of kinship terms, roles, and responsibilities. The traditional Cheyenne kinship system emphasized familial relationships for the sake of childrearing and imparting traditional values of respect, reciprocity, and balance. Traditional principles of heške'estovestôtse (motherhood), héhe'estovestôtse (fatherhood), and méhósánestôtse (love) were the backbone of the Cheyenne family.